The texture of culture : an introduction to Yuri Lotman's semiotic theory - Semenenko, Aleksei (New York : Palgrave Macmillan, 2012)
'This book is an introduction to the semiotic theory of one of the most original thinkers of the twentieth century, the Russian literary scholar and semiotician Yuri Lotman. The book offers a new look at Lotman's profound legacy and attempts to demonstrate how Lotman's holistic theory, transcending the traditional boundaries of academic disciplines, offers a genuinely interdisciplinary approach to culture. This study also makes Lotman accessible to a larger audience not limited only to specialists in Slavic studies and semiotics, covering a wide range of topics, from artificial intelligence to the role of an individual in history'--
Includes bibliographical references : (pages [147]-170) and index.
Keywords: Lotman, IU. M. -- 1922-1993 -- Criticism and interpretation; Semiotics; Culture -- Semiotic models; Semiotics and literature; Mass media